`A(x)=7x^3-5x^2-7x+3-7x^3+5x^2+17x+27`
`A(x)=(7x^3-7x^3)-(5x^2-5x^2)+(-7x+17x)+(3+27)`
`A(x)=10x+30`
Cho `A(x)=0`
`=>10x+30=0`
`=>10x=-30`
`=>x=-3`
Vậy nghiệm của đa thức `A(x)` là `x=-3`
Đặt \(A\left(x\right)=0\)
\(\rightarrow7x^3-5x^2-7x+3-7x^3+5x^2+17x+27=0\)
\(\Leftrightarrow10x+30=0\)
\(\Leftrightarrow10x=-30\)
\(\Leftrightarrow x=-3\)
Vậy \(x=-3\) là nghiệm của đa thức \(A\left(x\right)\)
A(x) = 7x3 - 5x2 - 7x + 3 - 7x3 + 5x2 +17x +27
= 10x + 30
đặt A(x) = 0
<=> 10x + 30 = 0
<=> 10x = -30
<=> x = -3
vậy x = -3 là nghiệm của A(x)